The Key Success of Local Staple Food Development Program: A Financial Comparison Study on Rice-Analog "Beras Siger" Business in Lampung - Fitriani Fitriani; Ambya Ambya; Sutarni Sutarni; Teguh Budi Trisnanto; Fadila Marga Saty; Rini Desfaryani (Inovbiz: Jurnal Inovasi Bisnis, 2022)
MSMEs play an important role in the success of community food diversification. Diversification of cassava food into rice substitution is known as analogue rice, in traditional terms it is called "tiwul". The Local Staple Food Development Model (MP3L) in Lampung Province introduced tiwul as a rice analog with the label "beras-siger". This study was conducted to compare and analyze the structure of costs and revenues, as well as the financial viability of Rice-analog that is produced by SMEs. The research location was Margomulyo Village, Jati Agung sub-district, South Lampung Regency as participants in the MP3L program. Non-participating MSMEs were in the production centers of East Lampung, Central Lampung, and Tulang Bawang districts. The business criteria assessment method from the financial aspect is used to determine the condition of financial feasibility. The results showed that the cost structure for participants and non-program participants differed in the value component of production equipment. The participants of the beras-siger business program are not eligible yet. Financial feasibility could reach through fulfilling the production capacity as installed capacity of production equipment. While the non-program participants are financially viable. Non-participant program entrepreneurs are relatively resilient to the changes in input prices and decreases in output prices. Beras-siger SMEs can be a strong basis for rural bio-industry development.